The Bangladesh economy in transition - Quibria, M. G. (Muhammad Ghulam); Asian Development Bank. (Dhaka : University Press limited, 1997)
Revised version of papers presented in a conference held in Bangladesh, 1993, organized by the Asian Development Bank in collaboration with the Academy for Planning and Development, Bangladesh.
Includes bibliographical references and index.
Keywords: Bangladesh -- Economic conditions -- Congresses; Bangladesh -- Economic policy -- Congresses